2014
DOI: 10.1073/pnas.1403135111
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the extended CAP-Gly domains of p150 glued binding to microtubules and the implication for tubulin dynamics

Abstract: Significance This study presents a direct visualization of the microtubule-p150glued(CAP-Gly) complex by cryo-EM and seeks to describe the molecular mechanism of the control of tubulin dynamics by p150 CAP-Gly. It highlights the neutralization of the acidic tubulin surface by the basic extensions of CAP-Gly, resulting in the activation of tubulin polymerization. In the condition where the lateral association is impeded (i.e., at low temperature), the extended CAP-Gly domain induces tubulin dimers to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 34 publications
3
64
0
Order By: Relevance
“…Our current results also clearly indicate that the bean-shaped CAP-Gly molecule binds to the microtubules with its flat surface comprised by its loops, the C-terminal β4-strand, and the short α-helix. These findings are in agreement with the recent cryo-EM results on the CAP-Gly(1-105)/MT and CAP-Gly(25-144)/MT complexes (40), which revealed the same flat side of CAP-Gly that forms the interface, including the proposed interaction of the GKNDG motif with the C terminus of tubulin. Of note, most of the surface-exposed, hydrophobic residues are on the flat side of CAP-Gly and are likely important for promoting the binding interaction.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our current results also clearly indicate that the bean-shaped CAP-Gly molecule binds to the microtubules with its flat surface comprised by its loops, the C-terminal β4-strand, and the short α-helix. These findings are in agreement with the recent cryo-EM results on the CAP-Gly(1-105)/MT and CAP-Gly(25-144)/MT complexes (40), which revealed the same flat side of CAP-Gly that forms the interface, including the proposed interaction of the GKNDG motif with the C terminus of tubulin. Of note, most of the surface-exposed, hydrophobic residues are on the flat side of CAP-Gly and are likely important for promoting the binding interaction.…”
Section: Resultssupporting
confidence: 92%
“…Recently, a cryo-EM study reported the structure of several CAP-Gly constructs on polymerized MTs at 9.7-10.2 Å resolution (40). Although atomic resolution was not achieved in this study, several important observations were made: (i) The interface of CAP-Gly with MT includes the GKNDG motif, which interacts with the C terminus of tubulin; (ii) the tubulin E-hooks interact with the basic patches 1-25 and 106-144 of the protein, possibly permitting it to diffuse laterally to the next binding site; (iii) the orientation of CAP-Gly on MTs depends on the length of the construct used; and (iv) the recognition sites for CAP-Gly and EB1 on tubulin are nonoverlapping.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, it will be interesting to study how p150 interacts with the microtubule in its GTP‐bound state as this is likely the relevant configuration for transport initiation. It will be interesting to understand how this interaction mode compares to the reported structure of the p150 CAP‐Gly domain and its neighbouring acidic region binding in a flexible manner to the C‐terminal tubulin tails of GDP/taxol microtubules (Wang et al , 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Because the association of the CENP-E C-terminal kinetochore-binding domain with microtubules depends little (20% reduction) on tubulin C-terminal tails [370], these results suggest that microtubule detyrosination directly regulates recognition by the CENP-E motor domain. In contrast, the recognition of tyrosinated microtubules by Dynein has been shown to involve p150/Dynactin [358,360] and structural reconstructions have indicated that this interaction is mediated by the GKNDG motif on the CAP-Gly domain of p150/Dynactin [371,372]. …”
Section: Mechanisms Of Chromosome Congressionmentioning
confidence: 99%